Traditional medicinal plant use in Loja province, Southern Ecuador - Sharon Douglas; Bussmann Rainer W (BMC, 2006)
Abstract This paper examines the traditional use of medicinal plants in Loja province, Southern Ecuador. Two hundred fifteen plant species were collected, identified and their vernacular names and traditional uses recorded. This number of species indicates that the healers, market vendors and members of the public interviewed still have a very high knowledge of plants in their surroundings, which can be seen as a reflection of the knowledge of the population in general. However, the area represents only an outlier of the larger Northern Peruvian cultural area, where more than 500 species of plants are used medicinally, indicating that in Ecuador much of the original plant knowledge has already been lost. Most plant species registered are only used medicinally, and only a few species have any other use (construction, fodder, food). The highest number of species is used for the treatment of "magical" (psychosomatic) ailments (39 species), followed by respiratory disorders (34), problems of the urinary tract (28), Fever/Malaria (25), Rheumatism (23) and nervous system problems (20).